AB0376 Gait assessment in patients with rheumatoid arthritis using the modular electronic baropodometer. (23rd January 2014) - Moreira, E.; Jones, A.; Oliveira, H.A.V.; Jennings, F.; Natour, J.
Abstract : Background: Rheumatoid arthritis (RA) is an auto-immune disease of unknown etiology, that can result in disability and a reduction in functionality. Gait alterations are common in patients with RA and it is associated with foot pain and deformity. Objectives: Assess gait variables in patients with RA and foot pain using the modular electronic baropodometer. Methods: Eighty female with RA between 18 and 65 years with a diagnosis of RA and foot pain ranging from 4 to 8 points on visual analogue scale (VAS) scale were analyzed. Patients with other musculoskeletal conditions in symptomatic lower limbs, conditions of the central or peripheral nervous systems, diabetes mellitus and an inability to walk were excluded. Evaluations were performed using a VAS for pain, the Health Assessment Questionnaire (HAQ), foot function index and six-minute walk test. Gait analysis was performed using AM Cube - FootWork Walk analysis system. The correlations between pain/function and baropodometer parameters were analysed. Results: Patients had a mean disease duration of 12.38 (7.82) years, diagnosis time of 11.09 (7.69) years and body mass index of 26.24 (4.82). These Patients 86.25% were functional class 1 and 13.75% functional class II, 65% were current use of disease modifying antirheumatic drug (DMARD) and biologics 35%.The data regarding clinical and baropodometer parameters were presented in table 1 . Conclusions: Function was correlated with almost all parameters of baropodometer, the bodily oscillation was the only parameter that did not show correlation with function. Pain was correlated with the parameters related to center of force and bodily oscillation in the sagittal plane. References: Van der Leeden M, Steultjens MP, Terwee CB, Rosenbaum D, Turner D, Woodburn J, Dekker J. A systematic reviw of instruments measuring foot function, foot pain, and foot-related disability in patients with rheumatoid. Arthritis Rheum 2008;59(9):1257-69. Simkin A. The dynamic vertical force distribution during level walking under normal and rheumatic feet. Rheumatol Rehabil 1981;20:88–97. Disclosure of Interest: None Declared